Calculator Provision as an Accommodation for the Canadian Forces Aptitude Test (CFAT) - Joseph Berry (Personnel Assessment and Decisions, 2024)
The impact of calculator provision on the reliability and validity of a version of the Canadian Forces Aptitude Test—Problem Solving subtest was investigated in order to inform testing accommodation policy. Two hundred and fifty-four Canadian Armed Forces recruits undergoing basic training participated in the experimental research design, which consisted of a calculator and a no-calculator condition. Results supported that the convergent validity of the test was maintained in the calculator condition, as indicated by similar validity coefficients with other measures of cognitive ability in the two conditions; however, several items showed increased correct responding, and there was mixed support for criterion-related validity when calculators were provided. Additionally, the calculator condition moderated the relationship between calculator dependency and test performance, such that the relationship was positive in the calculator condition and negative in the no-calculator condition. Implications of these results with respect to accommodation policy are discussed, as well as additional research that would be beneficial in this area.